Vitamin D status in children with COVID-19: does it affect the development of long COVID and its symptoms? - Perestiuk, Vita; Kosovska, Tetyana; Dyvoniak, Olha; Volianska, Liubov; Boyarchuk, Oksana (Frontiers in Pediatrics, 2025)
IntroductionLong COVID is characterized by diverse symptoms persisting after severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Given the immunomodulatory and neuroprotective properties of vitamin D, understanding its role in long COVID symptoms is of growing interest. This study aimed to determine vitamin D status in children with COVID-19 and assess its impact on the clinical course of disease and long COVID development.MethodsA prospective cohort study included hospitalized children with confirmed COVID-19, aged 1 month to 18 years, diagnosed between September 2022 and March 2024. Serum 25-hydroxyvitamin D (25(OH)D) concentrations were measured upon hospital admission, and follow-up was done to identify long COVID symptoms.ResultsIn total, 162 hospitalized patients with COVID-19 were examined. Vitamin D deficiency was determined in 8.0%, insufficiency in 25.3%, and optimal levels in 66.7% of children with COVID-19. Vitamin D deficiency/insufficiency was observed in 73% of children over 6 years and 21.6% of children under 6 years of age. Comorbid conditions were 1.4 times more frequent in children with vitamin D insufficiency, with undernutrition and obesity playing the most significant roles (p = 0.0023, p = 0.0245, respectively). Serum 25(OH)D concentration depends on COVID-19 severity (p = 0.0405) and children with vitamin D deficiency/insufficiency had a longer hospital stay (4 vs. 3 days, p = 0.0197). The vitamin D status affected the median levels of neutrophils, lymphocytes, their ratio, prothrombin time, fibrinogen levels, and the frequency of increased immunoglobulins M and E levels. Among 134 children who agreed to follow up, 56 (41.8%) experienced long COVID symptoms, while 78 (58.2%) recovered fully. Long COVID was frequently observed in children with vitamin D deficiency/insufficiency (p = 0.0331). The odds of developing long COVID were 2.2 times higher (p = 0.0346) in children with vitamin D deficiency/insufficiency compared to those with optimal levels. Children with vitamin D deficiency/insufficiency more often exhibited neurological (80% vs. 41.9%, p = 0.0040) and musculoskeletal symptoms (16% vs. 0%, p = 0.0208).ConclusionThe 25(OH)D concentrations in children with COVID-19 depended on their age. Comorbid conditions affect the vitamin D status in children with COVID-19. Vitamin D influenced the COVID-19 severity and duration of hospitalization. There was an increased risk of developing long COVID in children with vitamin D deficiency/insufficiency, and its impact on the development of neurological symptoms associated with long COVID was established.